Factors Predicting Quality of Life in Prisoners with Non – Communicable Diseases in the Lower Southern Province of Thailand - Chramnanpho, Punnaphat; Nakahro , Janwit (Journal of Nursing, Siam University, 2023)
Objectives: This study aimed to examine the factors predicting prisoners’ quality of life with non-communicable diseases (NCDs). Methods: This research employed a predictive correlational design and included a sample group of 160 prisoners with NCDs in the lower southern province of Thailand. Data were collected using a questionnaire and analyzed using descriptive statistics and multiple regression analysis. Results: The research results indicate that, in the sample group aged 41 to 60, individuals experiencing mild depression have a statistically significant correlation with a significant decrease in quality of life, with a log-odds of 2.269 (p = 0.001) when compared to the group of non-depressed individuals among those subject to compulsory military service. Meanwhile, the sample group with moderate depression shows a correlation with a decrease in quality of life, with a log-odds of 1.245 (p = 0.057). On the other hand, the sample group with severe depression or chronic diseases does not exhibit a statistically significant correlation with the quality of life. Conclusion and recommendations: To enhance the quality of life for prisoners with NCDs, it is important to address the impact of chronic illness and depression. By doing so, prisoners with NCDs can experience an improved quality of life, increased self-care, and better ability to carry out daily activities.